Two Different β3 Cysteine Substitutions Alter αIIbβ3 Maturation and Result in Glanzmann Thrombasthenia - Milet-Marsal, S.; Breillat, C.; Peyruchaud, O.; Nurden, P.; Combrié, R.; Nurden, A.; Bourre, F. (Thrombosis and Haemostasis, 2002)
We report the defects responsible for Glanzmann thrombasthenia in two patients showing traces of abnormally migrating platelet β3 in immunoblotting. Using PCR-SSCP and direct sequencing, we identified a novel homozygous mutation in exon 10 of the β3 gene of patient 1 which gave a C457 to Y amino acid substitution. A C542 to R substitution in β3 of patient 2 was previously reported by us. These cysteines are present in EGF-domains 1 and 3 respectively of β3. We therefore constructed mutants carrying substitutions on cysteine residues in each of the first three EGF domains of β3, C457, C495 and C542 respectively. Transient expression of these mutants in COS-7 cells, including the C542 and C547 double mutant, proved that disulfide disruption directly affects cell surface expression of the integrin. We then showed by metabolic (35S) labeling and Endo-H glycosidase treatment that these substitutions strongly affected complex maturation within the cell.
Keywords: Glanzmann thrombasthenia; platelet; αIIbβ3 integrin; cysteine mutations; Cos-7 cells